Efektivitas Pelatihan Keterampilan Dalam Menumbuhkan Minat Wirausaha Wanita Melalui Motivasi Diri Berwirausaha - Vembri Aulia Rahmi; Roziana Ainul Hidayati (JMK (Jurnal Manajemen dan Kewirausahaan), 2019)
The study intends to prove whether skills training (short courses), such as make up training can provide an effective role in fostering women's entrepreneurial intention.. Based on the latest data from IWAPI (Indonesian Women's Entrepreneurial Association), women have a significant role in contributing to the country's economy through its entrepreneurial activities. it is hoped that later it will provide understanding of how training can foster entrepreneurial intention for women. Path analysis with SPSS is used to test how the direct influence of training on entrepreneurial intentions and the indirect influence of training on entrepreneurial intentions through self-motivation in entrepreneurship. The results explained that the direct effect of skills training on entrepreneurial intentions showed a greater proportion than the indirect effect of skills training on entrepreneurial intentions through self-motivation in entrepreneurship. The effect of skills training with self-motivation of entrepreneurship simultaneously on entrepreneurial intentions shows that the skills training variable is not significant. It occurs because training is carried out in a short time, in which practice makeup skills require regular periodic training and assistance.